A promoter library for tuning gene expression in Cupriavidus necator under autotrophic conditions - Kitagawa, Wataru; Igarashi, Kensuke; Nagasawa, Ryo; Kakizawa, Shigeyuki; Horino, Mizuki; Fujishima, Kosuke; Fukui, Toshiaki; Kato, Souichiro (Frontiers in Bioengineering and Biotechnology, 2025)
Cupriavidus necator holds promise for biomanufacturing using CO2 as the primary feedstock, leveraging its capabilities to produce valuable chemicals and grow autotrophically using H2 as an energy source. Although various genetic tools, including promoters, have been developed to fine-tune gene expression in C. necator, no such tools have been developed for the use in autotrophic conditions. This study aimed to establish a promoter library that functions in C. necator grown under autotrophic conditions. C. necator was cultured under both heterotrophic and autotrophic conditions, and comparative transcriptome analysis was performed to identify genes/operons specifically upregulated under autotrophic conditions and those constitutively expressed. The upstream sequences of the candidate genes/operons were examined to identify their promoter regions. We established a promoter evaluation system based on colorimetric measurement of β-galactosidase activity in C. necator. Utilizing this system, we successfully identified seven promoters that specifically upregulate the downstream gene encoding β-galactosidase under autotrophic conditions and three promoters that constitutively express the gene under both autotrophic and heterotrophic conditions. We designed expression gene cassettes in which exogenous genes are placed downstream of the autotrophic-specific promoters and constructed a C. necator strain with the gene cassettes inserted into the genome. Quantitative RT-PCR analysis confirmed the expression of the exogenous genes under autotrophic conditions. This study represents the first development of a promoter library that functions in C. necator under autotrophic conditions without the need for specific external inducers. This advancement lays the groundwork for more efficient CO2-based biomanufacturing platforms, contributing to the development of sustainable bioprocesses.